The optimization concept of service fulfillment measurement: a research on surgery care - Nordin, Norshahrizan; Che Razak, Razli; Abdullah, Sharmini; Saraih, Ummi Naiemah; Marniati, Marniati; W. Muhamad Radzi, Wan Norsyafawati (2018)
This paper presents an optimization concept of service fulfillment measurement. Service delivery is assumed free from constraint, while service fulfillment is expected to achieve by maximizing the customer preferences. As the constraints are considered, the customer preferences are developed in a form of new model to set the optimum level of variables. The concepts will be further improved for medium and large scale optimization, which capable to evaluate the customer requirement in Kano-QFD integration. The results were also validated based on Kano Model and Quality Function Deployment (QFD) is integrated for patient attribute and service attribute prioritization. The new non-linear KanoQFD service satisfaction model has been developed, tested and validated with Kano model to facilitate the analysis and decision making for better service delivery improvement.